The Mastery of Prepositions for and to Among the Sixth Semester Students at English Letters Department of Sanata Dharma University - I Made Alvianto Putra Palamba; Anna Fitriati (Journal of Language and Literature, 2016)
This research aims to measure the mastery of prepositions for and to among the sixth semester students at English Letters Department of Sanata Dharma University. The researcher is also eager to identify whether or not the students find difficulties to decide which prepositions (for or to) they should use in making a correct sentence, especially in translating the Indonesian prepositions untuk, kepada, ke, buat and bagi into English. This will be related to certain conditions in which the students first language (mother tongue) influences their second language learning. Thus, it is also very important to find out whether or not the students are influenced by their first language (Indonesian) in second language (English) learning process. Keywords: prepositions, errors, mastery, accuracy